Монолатеральна спінальна анестезія у судинній хірургії однієї доби - Григор'єв, Сергій Володимирович; Балдін, І. А.; Григорьев, С. В.; Балдин, И. А.; Grigoryev, S. V.; Baldin, I. A. (Українська медична стоматологічна академія, 2018)
Резюме. Мета. Дослідити вплив монолатеральної спінальної анестезії (МСА) при виконанні флебектомій на одній нозі та ендоваскулярних ангіопластік, на інтраопераційний стан пацієнтів (ефективність, гемодинаміку, періопераційний озноб, потребу у катетерізації січового міхура, потребу у додатковій аналгоседації та задоволення анестезією), визначити потрібну кількість місцевого анестетику у порівнянні з неселективною спінальною анестезією (СА). Висновки. Зменшення дози місцевого анестетика бупівакаіну до 7,5 мг і одностороння латералізація його ефекту дозволяє зменшити негативні гемодинамічні та вегето-десімпатичні ефекти з повним збереженням його цільових анестетичних властивостей. Так, МСА сприяла оптимізації кардіогемодинаміки на 19,4% частіше, дозволила зменшити інтраопераційний озноб та тремтіння на 22%, сечовий катетер встановлювали на 12% рідше, ніж при традиційній спінальній анестезії. Отже, монолатеральна спінальна анестезія має суттєві переваги за декількома показниками, що дозволяє визначити вищу безпеку та комфорт для пацієнтів у порівняні з неселективною методикою СА. Резюме. Цель. Исследовать влияние монолатеральной спинальной анестезии (МСА) при выполнении флебектомий на одной ноге и эндоваскулярных ангиопластик, на интраоперационное состояние пациентов (эффективность, гемодинамику, периоперационный озноб, потребность в катетеризации мочевого пузыря, потребность в дополнительной аналгоседации и удовлетворение анестезией), определить необходимое количество местного анестетика по сравнению с неселективной спинальной анестезией (СА). Выводы. Уменьшение дозы местного анестетика бупивакаина до 7,5 мг и односторонняя латерализация его эффекта позволяет уменьшить негативные гемодинамические и вегето-десимпатизационные эффекты с полным сохранением его целевых анестетических свойств. Так, МСА способствовала оптимизации кардиогемодинамики на 19,4% чаще, позволила уменьшить интраоперационный озноб и дрожь на 22%, мочевой катетер устанавливали на 12% реже, чем при традиционной спинальной анестезии. Таким образом, монолатеральная спинальная анестезия имеет существенные преимущества по нескольким показателям, что позволяет определить высокую безопасность и комфорт для пациентов по сравнению с неселективной методикой СА. Abstract. The surgical activity, the quantity and quality of surgical interventions in vascular surgery are continuously increasing, which dictates the corresponding qualitative needs for anesthetic support – selectivity, rate of performance, safety, comfort for patients and fast recovery of motor and vegetative functions after the end of surgery. Goal. To investigate the effect of monolateral spinal anesthesia (MSA) with unilateral phlebectomy or endovascular surgery on the intraoperative state of patients (efficacy, hemodynamics, perioperational chills, the needs for catheterization of the urinary bladder, requesting additional analgesia and satisfaction with anesthesia), to determine the required amount of local anesthetic compared with nonselective spinal anesthesia (SA). Object and methods. The study involved 42 patients. 26 patients performed monolateral spinal anesthesia, 16 patients got nonselective spinal anesthesia. 28 women and 14 men, the average age of patients was 46.3 ± 7.32. Criteria for inclusion in the study were considered agreement of the patient and predicted the time of routine phlebological or endovascular intervention in less than 160 minutes. Monolateral anesthesia was performed in the position on the side, an average of 7.5-10 mg of hyperbaric bupivacaine was injected (marcain “Heavy” 0.5%) after the administration of the anesthetic, keeping the position on the side for at least 12 minutes. Non-selective spinal anesthesia was performed routinely, the average dose of isobaric bupivacaine (agitan 0.5%) was calculated according to the standard method, which averaged 12.5-15 mg. To evaluate the quality of anesthesia, the visual analog scale of pain (VAS) was used in 8 stages: before surgery, incision, end of operation, 1 hour after surgery, 3 hours, 5 hours, 7 hours, 24 hours accordingly. The centimeters of test correspond to the VAS scores. The Bromage scale was used to assess the effectiveness of the sensor-motor unit. For haemodynamically important changes in blood circulation, bradycardia was considered to be less than 55 beats per minute, or requiring re-administration of cholinolytics (excluding premedication) and / or arterial hypotension (SAT ≤ 60 mm Hg) that developed after standard preinfusion preparation, which required the re-introduction of mesatone. Satisfaction with anesthesia was assessed at the stages of intervention according to patients’ responses: yes/no, the number of complaints. The data processing was performed using the statistical packages of MS Office 2007, 2010 and Statistica 10, StatSoft. Results. Before the intervention, after the bandage of the lower extremities and placement on the operating table, the level of VAS in both groups did not exceed 1.5 points. At the end of the surgical intervention VAS mark did not exceed 1 point. For 1 hour of the postoperative period, the statistical difference between the groups is not defined. At 3 hours after the intervention, the VAS level exceeded the baseline. From 3 hours after surgical intervention and until the next day, statistically significant changes were not observed, the assessment for VAS on average did not exceed 2 centimeters. Differences in post-operative analgesia in the study groups were not observed. After the introduction of a low dose of bupivacaine for monolateral anesthesia, cases of chills with a tremor at the main stage of surgical intervention were found to be significantly lower approximately in 22 %. At the end of operative treatment and non-selective spinal anesthesia, sympatholytic tremor was saved on average 11% more often than with monolateral spinal anesthesia. Delay of urine after MSA in the postoperative period significantly decreased, which was determined in independent urination on average 164 ± 12 minutes after the end of the intervention, in groups of non-selective MSA urinating through 280 ± 21 minutes. With the use of monolateral spinal anesthesia, the overall need for catheterization of the bladder decreased by 13%, which directly affected the determination of a higher level of comfort with monolateral spinal anesthesia. Conclusions. Reducing the dose of local anesthetic bupivakain (7,5 mg) sided lateralization and its effect can reduce negative side effect of desimpatyzation with full preservation of its target anestetic properties. MSA found greater (19,4%) cardiodinamic protective effect against non selective spinal anesthesia, more effective reduce chills and shivering (22%), and the urinary catheter installed less than in 12% in comparison with non-selective spinal anesthesia. So monolateral spinal anesthesia has a substantial advantage in more than 5 indicators to determine the highest safety and comfort for patients as compared to non-selective method of SA.
Монолатеральная спинальная анестезия в сосудистой хирургии одного дня
Monolateral spinal anesthesia in one day vascular surgery
Keywords: спинномозкова анестезія; однобічна спінальна анестезія; періопераційний озноб і тремтіння; ускладнення спінальної анестезії; спинальная анестезия; односторонняя спинальная анестезия; периоперационный озноб и дрожь; осложнения спинальной анестезии; spinal anesthesia; monolateral spinal anesthesia; perioperational chills and shivers; spinal anesthesia complications